2017
DOI: 10.1021/acs.jpcc.7b03622
|View full text |Cite
|
Sign up to set email alerts
|

Lyotropic Liquid-Crystalline Mesophase of Lithium Triflate–Nonionic Surfactant as Gel Electrolyte for Graphene Optical Modulator

Abstract: Lithium salt (noncoordinating anions, such as lithium triflate (Ltf)) gel electrolytes may be key for the practical use of electrochemical devices. We introduce a new lyotropic liquid-crystalline (LLC) mesophase using Ltf, a small amount of water (as low as 1.3 water per Ltf), and nonionic surfactant (C 18 H 37 (OCH 2 CH 2 ) 10 OH, C 18 E 10 ). The LLC phase forms over a broad range of Ltf/C 18 E 10 mole ratios, 2−18. The clear ethanol solution of the ingredients can be either directly spin-coated over a glass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
6
0
1
Order By: Relevance
“…In our previous studies, it has been shown that a LiX salt (X could be Cl – , Br – , I – , NO 3 – , and CF 3 SO 3 – ), a nonionic surfactant, and a small amount of water form a lyotropic liquid crystalline (LLC) mesophase and may be used as an electrolyte in various electrochemical cells. The LiI–I 2 redox couple, used in DSSCs, and 10-lauryl ether (C 12 H 25 (OCH 2 CH 2 ) 10 OH, denoted as C 12 E 10 ) also form an LLC mesophase and could be used as a gel electrolyte in DSSCs . The major issue of the LLC gel electrolytes is that it is difficult to effectively combine the gel electrolyte and DSSC electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, it has been shown that a LiX salt (X could be Cl – , Br – , I – , NO 3 – , and CF 3 SO 3 – ), a nonionic surfactant, and a small amount of water form a lyotropic liquid crystalline (LLC) mesophase and may be used as an electrolyte in various electrochemical cells. The LiI–I 2 redox couple, used in DSSCs, and 10-lauryl ether (C 12 H 25 (OCH 2 CH 2 ) 10 OH, denoted as C 12 E 10 ) also form an LLC mesophase and could be used as a gel electrolyte in DSSCs . The major issue of the LLC gel electrolytes is that it is difficult to effectively combine the gel electrolyte and DSSC electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…This work is an important extension of LiA:C 12 E 10 : H 2 O LLC materials, where LiA is LiCl, LiBr, LiI, LiNO 3 , LiSCN, LiSO 3 CF 3 etc. [6,13,17] Note that all above LiX salts have good solubility in aqueous media. Especially, with the help of CE, the solubility limits of these salts can be further improved to accommodate an extensive amount of LiA species in the hydrophilic domains of a salt-surfactant LLC mesophase.…”
Section: Resultsmentioning
confidence: 99%
“…Было установлено, что жидкокристаллическая мезофаза чувствительна к типу аниона в применяемых солях и ионной силе среды. В настоящее время эти исследования продолжаются; металлсодержащие лиотропные ЖК успешно используются в качестве темплатов для получения мезопористых солей ванадия, лития и других элементов [108][109][110]. Применение в качестве лигандов переходных металлов находят и катионные ПАВ.…”
Section: металломицеллярные системы на основе пав с глюкаминовым фрагunclassified